Mapping the scholarly landscape of lifestyle migration in tourism: bibliometric patterns of trend, themes and future directions - Maja Niksić Radić; Daniel Dragičević (Eastern Journal of European Studies)
This study analyses the evolution and intellectual structure of lifestyle migration research in tourism through bibliometric analysis. Despite its growing relevance, no systematic review has mapped the intersection of these fields. To address this gap, we have examined 145 publications indexed in the Web of Science (1990-2023) using VOSviewer. The findings identify key contributors, thematic clusters, and emerging research directions. The analysis reveals four dominant themes: migration and socio-economic impacts, tourism-driven mobility, transnational lifestyle patterns, and second-home tourism. Research output has grown significantly since 2010, with Spain and the USA leading contributions. The study highlights an increasing focus on digital nomadism, tourism gentrification, and sustainability. Future research should explore lifestyle migration's socio-economic effects, digital infrastructure's role, and policies that balance migration-driven tourism with sustainability. By providing the first structured bibliometric synthesis, this study offers theoretical insights and practical implications for policymakers and tourism practitioners.